(untitled) (Research, Society and Development, 2024)
Objective: to carry out an integrative literature review to propose a concept for the term Pharmaceutical Gerontology. In this sense, the research’s guiding question is observed - what is the importance of a proposal for the concept of pharmaceutical gerontology? Methodology: This is an exploratory and descriptive study of the integrative literature review type. Selection carried out in the databases PubMed, Medical Literature Analysis and Retrieval System Online (MEDLINE) and Latin American and Caribbean Literature in Health Sciences (LILACS) and Periodicals Capes, through the descriptors located in Descriptors in health sciences (DeCS /MeSH): Gerontology, Geriatrics, Pharmacy, Concept, Concept formation, Pharmaceutical Care, Clinical pharmacy services, Pharmaceutical care, Pharmaceutical care, Elderly and Elderly health in Portuguese, English and Spanish between the years 2012 to 2021. Results: The results were organized in tables and charts, PRISMA and Iramuteq flowchart for better observation. Having 4,477 articles found. Thus, after reading in order to answer the guiding question, only 15 articles were successful. Discussion: The study does not present results in the selected articles on a concrete concept for the term Pharmaceutical Gerontology, it is only possible to categorize suggestions obtained in the considerations of the studies that were selected for the integrative review. Final considerations: Defining the concept of Pharmaceutical Gerontology will facilitate the student’s and professional’s understanding of the unique health needs of the elderly and what attributes the pharmacist is inserted to promote the quality of life of this patient.